(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In this article, with increased endurance issues such as maintaining high-level working ability of the organism, education of coordination of movement, breathing, blood circulation, development of movement functions, role of physical education in the formation of personality, ability of coordination of movement during the training of a basketball player are disclosed.